2020
DOI: 10.3390/e22050495
|View full text |Cite
|
Sign up to set email alerts
|

Aspects of Chemical Entropy Generation in Flow of Casson Nanofluid between Radiative Stretching Disks

Abstract: The appropriate utilization of entropy generation may provoke dipping losses in the available energy of nanofluid flow. The effects of chemical entropy generation in axisymmetric flow of Casson nanofluid between radiative stretching disks in the presence of thermal radiation, chemical reaction, and heat absorption/generation features have been mathematically modeled and simulated via interaction of slip boundary conditions. Shooting method has been employed to numerically solve dimensionless form of the govern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
25
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(25 citation statements)
references
References 39 publications
0
25
0
Order By: Relevance
“…Hayat et al [29] investigated the flow of Ree-Eyring nanofluid with entropy generation and Arrhenius activation energy with binary chemical reaction between two rotating disks where velocities are boost up with higher values of Reynolds number while both the entropy generation rate and Bejan number are decreased at lower disk. Khan et al [30] modeled and solved the problem of entropy generation in rotating flow of Casson nanofluid between stretching disks in the presence of thermal radiation, chemical reaction, heat source/sink with slip boundary conditions. Their simulation results revealed that axial velocity and Bejan number are diminished with the increments of Casson nanofluid parameter.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hayat et al [29] investigated the flow of Ree-Eyring nanofluid with entropy generation and Arrhenius activation energy with binary chemical reaction between two rotating disks where velocities are boost up with higher values of Reynolds number while both the entropy generation rate and Bejan number are decreased at lower disk. Khan et al [30] modeled and solved the problem of entropy generation in rotating flow of Casson nanofluid between stretching disks in the presence of thermal radiation, chemical reaction, heat source/sink with slip boundary conditions. Their simulation results revealed that axial velocity and Bejan number are diminished with the increments of Casson nanofluid parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Khan et al. [30] modeled and solved the problem of entropy generation in rotating flow of Casson nanofluid between stretching disks in the presence of thermal radiation, chemical reaction, heat source/sink with slip boundary conditions. Their simulation results revealed that axial velocity and Bejan number are diminished with the increments of Casson nanofluid parameter.…”
Section: Introductionmentioning
confidence: 99%
“…Ahmad and Nadeem [39] used the Thomson and Troian auxiliary conditions to investigate the entropy minimization in stagnation point flow of a hybrid nanofluid with Cattaneo-Christov heat and mass flux theory, variable mass diffusivity and viscosity, activation energy past a nonlinear porous stretching sheet. Khan et al [40] applied the shooting method to compute the solution of entropy generation in axisymmetric flow of non-Newtonian nanofluid between two parallel rotating disks where Bejan number was noted to decrease with increasing the parameter of Casson nanofluid. Khan et al [41] examined the entropy generation for single/multi walled carbon nanotubes with homogeneous-heterogeneous chemical reactions and heat transfer.…”
Section: Introductionmentioning
confidence: 99%
“…In this examination, they likewise viewed warm radiation and thick dispersal impacts for the stream framework over an extending sheet. Khan et al 37 have contemplated the impacts of synthetic entropy optimization on the axisymmetric flow of Casson nanoliquid between radiative extending plates with warm radiation, chemical response, and temperature that have been scientifically demonstrated and re‐created by means of the collaboration of slip limit conditions. Liao 38,39 has recognized that this strategy is fast convergent to the estimated solution, and for the result of nonlinear problems, it is more acceptable.…”
Section: Introductionmentioning
confidence: 99%